Unsuspected Stewart–Treves syndrome clinically mimicked by apparent bullous erysipelas and a systematic review of dermatological presentations of the classical Stewart–Treves syndrome. Issue 2 (25th October 2018) - da Costa Vieira, René Aloisio; de Araujo Silva, Igor; de Oliveira‐Junior, Idam; de Almeida Santos Yamashita, Mauricio Eiji; da Silva, Sandra Regina Morini
Abstract: Background: Stewart Treves–Syndrome (STS) was first characterized as angiosarcoma in the homolateral limb of a patient with breast cancer and lymphedema. Now, other conditions represent STS. It's a rare condition. The diagnosis is easier in the presence of single or multiple purple nodules. Even though other dermatological aspects have been reported, no study has grouped its characteristics. Aim: Evaluate the dermatological characteristics of classical STS (c‐STS). Methods and Results: We report a patient with chronic lymphedema with a history of recurrent erysipelas that rapidly developed multiple papules in the superior limb. It was initially diagnosed as bullous erysipelas, but unsatisfactory evolution led to biopsy, which demonstrated an unsuspected epithelioid angiosarcoma. We have also performed a review of dermatologic aspects of c‐STS using PubMed and Lilacs databases. PICTOS methodology and PRISMA flow chart were considered. The main dermatological aspects associated with c‐CTS were summarized. Using a systematic evaluation from 109 articles, 29 were selected and 44 patients were described to whom we added one case. The mean time with lymphedema was 10 years. Of the patients analyzed, 97.2% were female; 95.6% were submitted to radical mastectomy; 81.2% presented with multiple lesions, 67.4% of the lesions were reported as nodules or tumors, 53.4% were purple, 33.4% were associated with an ecchymotic halo, and 33.4% were ulcerated lesions. Conclusion: When evaluating patients with chronic lymphedema with new dermatological abnormalities, clinical suspicion, or unfavorable evolution, the knowledge of clinical signs is important for diagnosis, and a biopsy must be considered. Papules associated with erythematous‐wine color and bluish hematoma aspect must raise clinical suspicion.